Serbian Traditional Spirit Enriched With Yellow Gentian and Saline Wormwood: Volatile Profile and Sensory Traits - Veljović, Sonja; Cvetković, Dragan; Petrović, Marija; Luković, Milica; Karabegović, Ivana; Vukosavljević, Predrag; Stevanović, Zora Dajić (Flavour and fragrance journal, 2025)
Since ancient times numerous, aromatic and medicinal herbs have been commonly used for the production of various herbal beverages. The effect of yellow gentian ( Gentiana lutea ) and saline wormwood ( Artemisia santonicum ) on the qualitative and quantitative composition of the volatile compounds and the sensory properties of the Serbian traditional plum brandy (“slivovitz”) was investigated. Simultaneously, similar commercial alcoholic beverages obtained from the local market have been researched for comparison. Eighty‐nine volatile compounds were detected by GC–MS analysis in tested herbal spirits. More than 30% of detected volatile compounds belong to esters, whereas fatty acid esters contributed to the flavour with pleasant fruity and floral notes. The addition of A. santonicum improved the complexity of volatile profiles, with the main contribution of ketones. On the other hand, the phenylethyl alcohol, typical for its pleasant odour, was exclusively detected in samples enriched by yellow gentian. Saline wormwood contains compounds of a higher influence on lightness compared to the gentian root, whose compounds have increased the red colour intensity of the alcoholic product. The volatile compounds of yellow gentian and saline wormwood enriched the sensory properties of alcohol spirits, both contributing to the fruity aroma, with differences in spicy and herbal aroma, respectively. Extractible compounds of the studied herbs increased the complexity of the volatile profile, which significantly improved the aroma of herbal spirits. Selected herbs, already known for their traditional ethnomedicinal uses in the Balkans, could be considered as valuable material for production of functional beverages of attractive sensory traits.